نسبةُ القولِ بجوازِ قَتْلِ الثُّلُثِ لاستصلاح الثُّلُثَيْنِ إلى الإمام مالك, تاريخُها, ومَوْقِفُ المُحَقِّقِّينَ منه - حب الحمص, فاتح (جامعة الوادي - University of Eloued, 2018)
في القرن الخامس الهجري نَسَبَ إمامُ الحرمين الجويني إلى الإمام مالك القولَ بجواز قتل الثلث لاستصلاح الثلثين, وتابَعَهُ على هذه النسبة جماعةٌ من الفقهاء, فرَدَّ عليهم علماءُ المالكية, وبَيَّنُوا أن هذا القول لا تصح نسبَتُه إلى الإمام مالك, ولم يقُلْهُ أحدٌ من المالكية, سوى ما أفتى به اللَّخْمِيُّ في مسألة السفينة, وهو من اجتهاداته الخاصة التي شَذَّ فيها عن مذهبه المالكي؛ وعليه فإنه لا يصح تاريخيا أن يُنْسَبَ هذا القولُ إلى الإمام مالك, وإن أفتى على وِفْقِه اللخمي. Summary: The imam of Al-Haramain al-Juwaini has attributed to Imam Malik the saying that it is permissible to kill one-third to reclaim the two-thirds, and this was followed by a group of fundamentalists, The scholars of the Maalikis responded to this, and clarified that this view is not valid for Imam Malik, Or any one from maalikis, except what was said by lakhmi in The issue of the ship, which is one of his own insights, which is a deviation from the doctrine of Maliki; and therefore it is not permissible to attribute to the Imam Malik this statement based on the fatwa of the lakhmi.
مقال
Keywords: مالِك, الجويني, اللخمي, الثلث, الثلثين, استصلاح, السفينة